Farmers' Savings Potential for Oil Palm Replanting: Key Influencing Factors - Livia Vinota; Maryadi; Agustina Bidarti (Universitas Muhammadiyah Malang, 2025)
Ensuring the sustainability of oil palm farming is crucial for maintaining farmers' income. Replanting serves as a vital strategy to sustain production and enhance productivity. However, the substantial financial requirements for replanting necessitate that farmers accumulate funds through personal savings. This study investigates the primary factors affecting smallholders' propensity to save for oil palm replanting. Conducted in Suka Damai Baru Village, Sungai Lilin Sub-district, Musi Banyuasin District, South Sumatra, Indonesia, the research employed a survey methodology. Data was collected through interviews and questionnaires administered to 50 respondents. Binary Logistic Regression was utilized for statistical analysis. The findings indicate that total household income significantly positively influences farmers' savings potential, with a significant level of 0.003 and a coefficient of 1.297. Conversely, the size of oil palm plantations exerts a significant negative impact on savings potential, with a significant level of 0.017 and a coefficient of -4.938. Additionally, the number of household members negatively affects savings potential, with a significant level of 0.050 and a coefficient of -1.306. In contrast, the age of farmers does not significantly affect their savings potential.